The public image of Eastern Orthodoxy France and Russia, 1848-1870 - Bailey, Heather L., 1969- (NIU series in Orthodox Christian studies., 2020)
"This book focuses on the public image of Orthodoxy as constructed by westerners (mainly French) and as imagined by Russian publicists in the 1850s and 1860s "--